(untitled) (KYAMC Journal, 2013)
Mrs Rojina Akter 27 years old lady presented to us with complains of 12 weeks amenorrhea with the history of Rheumatic heart disease(MS-severe with MR Gr-2+ with AR Gr-2) treated surgically with mechanical metallic Double valve Replacement on 7th April 2010 in Cardiac Surgery Department of KYAMCH. It was her second conception.first one was terminated by MR due to fear of cardiac problem out side of this hospital. She also noticed slight breathlessness & palpitation. On examination- she was anxious, her respiratory rate, pulse rate & blood pressure were within normal limits. Her ECG report was within normal limit & colour Doppler Echo study showed normally functioning prosthetic metallic valves in Aortic & Mitral position with normal ejection fraction. Under joint-consultation with Cardiologist & Obstetrician she was advised to continue her pregnancy with careful & regular antenatal check up. During antenatal period she continued her cardiac medications & other supplementary drugs for her pregnancy. Without some minor ailments she continued her pregnancy up to 38 wks, then she delivered a healthy female baby by caesarean section on 6th August 2012 .Now she is well under the supervision of Cardiologist. KYAMC Journal Vol. 3, No.-2, January 2013, Page 306-308 DOI: http://dx.doi.org/10.3329/kyamcj.v3i2.15173